2014
DOI: 10.2147/ndt.s57909
|View full text |Cite
|
Sign up to set email alerts
|

Effects of galantamine in a 2-year, randomized, placebo-controlled study in Alzheimer's disease

Abstract: BackgroundCurrently available treatments for Alzheimer’s disease (AD) can produce mild improvements in cognitive function, behavior, and activities of daily living in patients, but their influence on long-term survival is not well established. This study was designed to assess patient survival and drug efficacy following a 2-year galantamine treatment in patients with mild to moderately severe AD.MethodsIn this multicenter, double-blind study, patients were randomized 1:1 to receive galantamine or placebo. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 29 publications
2
47
1
1
Order By: Relevance
“…Similar to the present results, two previous placebo-controlled studies have demonstrated long-term beneficial effects of ChEI therapy 6,19. On the other hand, the Alzheimer’s Disease Neuroimaging Initiative (ADNI) and the Australian Imaging, Biomarkers and Lifestyle study obtained opposing results, with greater cognitive decline amongst AD patients taking ChEIs compared with those not using ChEIs 20.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to the present results, two previous placebo-controlled studies have demonstrated long-term beneficial effects of ChEI therapy 6,19. On the other hand, the Alzheimer’s Disease Neuroimaging Initiative (ADNI) and the Australian Imaging, Biomarkers and Lifestyle study obtained opposing results, with greater cognitive decline amongst AD patients taking ChEIs compared with those not using ChEIs 20.…”
Section: Discussionsupporting
confidence: 93%
“…However, the American cohort was considerably younger and better educated than the European cohorts. A recent 2-year randomized placebo-controlled trial reported lower mortality in a galantamine-treated group compared with placebo (3.2 vs. 5.5%) [27]. In the SATS, 5.9% of the individuals had died after 2 years, but their mean age at the start of ChEI therapy was 3 years older.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Hager et al (2014) reported that 437 patients taking memantine and 1375 AD patients not taking this drug were randomly assigned to galantamine or placebo and were followed-up for 2 years. In posthoc analysis of this study, among patients not taking memantine, the galantamine group showed a 1.12-point decrease on MMSE and the placebo group showed a 2.15-point decrease.…”
Section: Discussionmentioning
confidence: 99%